DISASTER MITIGATION LECTURE STRATEGY BASED ON CITIZEN SCIENCE PROJECT WITH A COMBINATION OF INDOOR AND OUTDOOR ACTIVITIES - Ekaputri, Rendi Zulni; Hidayat, Topik; Surtikanti, Hertien Koosbandiah; Surakusumah, Wahyu (Universitas Negeri Makassar, 2024)
This study aims to describe a disaster mitigation lecture strategy based on the Citizen Science Project (CSP) through a combination of indoor and outdoor learning methods. The study employs an action research approach by implementing a lecture strategy consisting of four phases: BuPAcE (Building Community, Project Expedition, Action, and Evaluate). This study involved 22 fifth-semester students from the Science Education Study Program in the 2023-2024 academic year. The Building Community, Action, and Evaluate phases are conducted using indoor learning methods, while the Project Expedition phase is carried out using outdoor methods. The implementation of the BuPAcE strategy is evaluated using observation sheets. The results indicate that the implementation percentage of the disaster mitigation lecture strategy based on CSP is 80% for the Building Community phase, 70% for the Project Expedition phase, 80% for the Action phase, and 75% for the Evaluate phase. Based on these results, it can be concluded that the disaster mitigation lecture strategy using a combination of indoor and outdoor methods is effective for use in lectures.